The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/j.1551-8833.1995.tb06427.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cryptosporidium, Giardia, and MS2 virus removal by MF and UF

Abstract: Protozoan removal was a function of size, whereas virus removal was influenced by physical straining or adsorption, cake layer formation, or the fouling state of the membrane. Water quality regulations dealing with microbial removal have increased interest in using microfiltration (MF) and ultrafiltration (UF) as barriers against protozoan cysts and viruses. Consequently, a study was conducted to evaluate the removal of these organisms by a variety of MF and UF membranes and to elucidate removal mechanisms. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(113 citation statements)
references
References 8 publications
7
106
0
Order By: Relevance
“…The most effective PACl dosage from a previous study did not suitably remove the concentration of bacteriophage Qβ. These results relate to those of [22] who noticed that increasing the concentration of bacteriophage in the feed solution from 10 6 to 10 9 PFU/ml caused more than a 1 log drop in removal using ultrafiltration. Thus, the bacteriophage Qβ in the feed water can have an effect on the removal of bacteriophage Qβ of ceramic membrane microfiltration with in-line coagulation.…”
Section: Removal Of Bacteriophage Qβ With Different An Initial Concensupporting
confidence: 86%
“…The most effective PACl dosage from a previous study did not suitably remove the concentration of bacteriophage Qβ. These results relate to those of [22] who noticed that increasing the concentration of bacteriophage in the feed solution from 10 6 to 10 9 PFU/ml caused more than a 1 log drop in removal using ultrafiltration. Thus, the bacteriophage Qβ in the feed water can have an effect on the removal of bacteriophage Qβ of ceramic membrane microfiltration with in-line coagulation.…”
Section: Removal Of Bacteriophage Qβ With Different An Initial Concensupporting
confidence: 86%
“…Liu et al [108] reported a 0.5 log reduction in removal by a membrane immediately after backwash, which increased until the next backwash. Jacangelo et al [109] noted that the virus removal by MF/UF membranes was low at the beginning of filtration and increased with time with accumulation of foulants. However, in that study, the removal rate did not decrease after hydraulic backwash, indicating that the irreversible membrane fouling maintained the virus removal.…”
Section: Impact Of Membrane Cleaningmentioning
confidence: 99%
“…However, more contradictory results were obtained when smaller pathogens like Cryptosporidium, Giardia and MS2 were considered [5,8,9].…”
Section: Introductionmentioning
confidence: 99%